Established Tumour Biomarkers Predict Cardiovascular Events and Mortality in the General Population - Bracun, Valentina; Suthahar, Navin; Shi, Canxia; de Wit, Sanne; Meijers, Wouter C.; Klip, IJsbrand T.; de Boer, Rudolf A.; Aboumsallem, Joseph Pierre (Frontiers in Cardiovascular Medicine, 2021)
Introduction: Several lines of evidence reveal that cardiovascular disease (CVD) and cancer share similar common pathological milieus. The prevalence of the two diseases is growing as the population ages and the burden of shared risk factors increases. In this respect, we hypothesise that tumour biomarkers can be potential predictors of CVD outcomes in the general population. Methods: We measured six tumour biomarkers (AFP, CA125, CA15-3, CA19-9, CEA and CYFRA 21-1) and determined their predictive value for CVD in the Prevention of Renal and Vascular End-stage Disease (PREVEND) study. A total of 8,592 subjects were enrolled in the study. Results: The levels of CEA significantly predicted CV morbidity and mortality, with hazard ratios (HRs) of HR 1.28 (95% CI 1.08–1.53), respectively. Two biomarkers (CA15-3 and CEA) showed statistical significance in predicting all-cause mortality, with HRs 1.58 (95% CI 1.18–2.12) and HR 1.60 (95% CI 1.30–1.96), when adjusted for shared risk factors and prevalent CVD. Furthermore, biomarkers seem to be sex specific. CYFRA 21-1 presented as an independent predictor of CV morbidity and mortality in female, but not in male gender, with HR 1.82 (95% CI 1.40–2.35). When it comes to all-cause mortality, both CYFRA and CEA show statistical significance in male gender, with HR 1.64 (95% CI 1.28–3.12) and HR 1.55 (95% CI 1.18–2.02), while only CEA showed statistical significance in female gender, with HR 1.64 (95% CI 1.20–2.24). Lastly, CA15-3 and CEA strongly predicted CV mortality with HR 3.01 (95% CI 1.70–5.32) and HR 1.82 (95% CI 1.30–2.56). On another hand, CA 15-3 also presented as an independent predictor of heart failure (HF) with HR 1.67 (95% CI 1.15–2.42). Conclusion: Several tumour biomarkers demonstrated independent prognostic value for CV events and all-cause mortality in a large cohort from the general population. These findings support the notion that CVD and cancer are associated with similar pathological milieus.